Ferredoxin III of Desulfovibrio africanus: sequencing of the native gene and characterization of a histidine-tagged form. - Busch, J; Breton, J; Davy, S; James, R; Moore, G; Armstrong, F; Thomson, A (2000)
Desulfovibrio africanus ferredoxin III (Da FdIII) contains one [4Fe-4S](2+/1+) cluster and one [3Fe-4S](1+/0) cluster, bound by seven Cys residues, in which the [3Fe-4S] cluster is co-ordinated by the unusual sequence, Cys(11)-Xaa-Xaa-Asp(14)-Xaa-Xaa-Cys(17)-Xaa(n)-Cys(51)-Glu. The [3Fe-4S] core of this ferredoxin is so far unique in showing rapid bi-directional [3Fe-4S]<-->[4Fe-4S] cluster interconversion with a wide range of metal ions. In order to obtain protein for mutagenesis studies Da FdIII has been cloned, sequenced, and expressed as a hexa-histidine tagged (ht) polypeptide in Escherichia coli strain BL21(DE3) pLysS. Expression of ht Da FdIII, whether translated from a synthetic gene (pJB10) or from the native nucleotide sequence (pJB11), occurred at similar levels (approx. 6 mg.l(-1)), but without incorporation of metal clusters. The nucleotide sequence confirms the protein sequence reported previously [Bovier-Lapierre, Bruschi, Bonicel and Hatchikian (1987) Biochim. Biophys. Acta 913, 20-26]. Cluster incorporation was achieved using FeCl(3) together with cysteine sulphur transferase, NifS, plus cysteine to generate low levels of sulphide ions. Absorption and EPR spectroscopy show that both [3Fe-4S] and [4Fe-4S] clusters are correctly inserted. Thin-film electrochemistry provides evidence that the [3Fe-4S] cluster undergoes reversible cluster transformation in the presence of Fe(II) and Zn(II) ions with properties identical to the native protein. Nevertheless the protein has lower stability than native Da FdIII during chromatography. The one-dimensional 600 MHz NMR spectrum of the apoprotein indicates an unstructured protein with random coil chemical shifts whereas spectra of the reconstituted ht protein show secondary structural elements and 18 peaks shifted downfield of 9.6 p.p.m. The spectra are unique but have similarities with the shift patterns seen with 7Fe Desulfurolobus ambivalens Fd. The ht does not affect iron-sulphur cluster incorporation, but NMR evidence suggests that excess Fe binds to the tag. This may account for the lower stability of the ht compared with the native protein.